Affordances and constraints of a blended learning course: experience of pre-service teachers in an African context - Yusuf Feyisara Zakariya; Kazaik Benjamin Danlami; Yusuf Olayinka Shogbesan (Humanities & Social Sciences Communications)
Abstract This article reports our deliberate effort to redesign a traditionally taught course for pre-service teachers to suit a blended learning approach. We designed the course following the resource-activity-support-evaluation pedagogical model. Then, we investigated pre-service teachers’ perceptions of the course using a qualitative method of generation and analysis at a university in Sub-Saharan Africa. We generated the data using semi-structured interviews of pre-service teachers who gave voluntary consent and followed the blended learning course for a semester. We analysed the generated data using thematic analysis to uncover the underlying meanings across the transcribed responses. The findings showed that pre-service teachers positively perceived the blended learning course. The course provided exposure to diverse digital resources and enhanced the development of conceptual knowledge. Results indicated improved motivation, attitudes, and interest in the learning content. The course enhanced personalised learning, collaboration and flexibility through recorded videos, group projects, and electronic materials. However, our findings also revealed some constraints that prevented actualising these affordances. These include internet instability, computer proficiency gaps, online interaction issues, power supply concerns, and limited computer access. We argued that the affordances of the blended learning course overshadowed its constraints, and we explained a framework for actualising these affordances.